Regional Variations in Social Development and Levels of Living A Study of the Impact of Plan Programmes Volume I - Planning Commission (Planning Commission, 1967)
In the context of the need for balanced development of the different parts of the country and extension of the benefits of economic progress to the less developed regions, a study on the level of development in different parts of the country and the growth thereof becomes important. A knowledge of the inter-State and inter-regional differences with regard to various socioeconomic indicators is thus necessary to devise appropriate measures for balanced development in successive Plan periods. A study of this nature was originally proposed by Prof. V.K.R.V. Rao in the meeting of the National Development Council held towards the end of 1963 and was later pursued at subsequent meeting with the Slate Planning Secretaries. The intention was to sponsor in each State a quick but fairly comprehensive study of the impact of planned development in different parts of the country on different aspects of the economy.
A Study of the Impact of Plan Programmes Volume I